Gerakan Koin NU Bentuk Pengejawantahan Ekonomi Kerakyatan Selaras Dengan Sistem Ekonomi Islam - Almunawaroh, Tri; Boby Sandityas Prahasto (DPPM Universitas Pelita Bangsa, 2025)
This literature review aims to understand the relationship between the NU Coin Movement and the people's economy and the Islamic economic system.The research data were obtained from various library sources, including books, articles, journals, official websites, and other scholarly writings.From the review of various sources, it can be understood that the NU coin movement is a movement for the independence of the community, where the funds collected from the NU community are managed by NU and used for NU. Its purpose is for the common welfare, to help the weak, empower the capable, and reduce social inequality among the community.The existence of a gotong royong system and the realization of people's sovereignty,